2019
DOI: 10.21203/rs.2.15882/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Joint Modelling of Colorectal Cancer Recurrence and Death after resection using Multi-State Model with Cured Fraction

Abstract: Background Curing of colorectal cancer (CRC) occurs at the time of resection, but it is not immediately observable. If the cancer is not completely eliminated, the patient will not be cured of cancer and will experience a recurrence as the tumor has regrown to a detectable size. The main proposes of the present study was to assess the effects of different covariates on the probability of being cured as well as the time to recurrence, time to death, and time to death after recurrence in CRC patients by using mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[26], some studies reported similar results [27][28]. Also, in some studies, age was signi cantly associated with local recurrence and distance [29][30] [31]. Also, according to the results of several studies, age is signi cantly associated with the survival of patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 83%
“…[26], some studies reported similar results [27][28]. Also, in some studies, age was signi cantly associated with local recurrence and distance [29][30] [31]. Also, according to the results of several studies, age is signi cantly associated with the survival of patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, evaluating RFS aims to estimate the probability of relapse by considering death as censoring. However, those separate analyses do not provide completely satisfying results due to a failure to reveal associations between relapse and death [12,13]. In contrast, the IDM simultaneously deals with endpoints focusing on transitioning from one state to another.…”
Section: Korean Cancer Associationmentioning
confidence: 99%
“…Several medical articles have estimated event-related predictive probabilities via the IDM in patients with breast cancer [12,14,15], ovarian cancer [16], or colon cancer [13]. However, to our knowledge, the IDM has not been implemented in patients with lung cancer.…”
Section: Korean Cancer Associationmentioning
confidence: 99%
“…Although early diagnosis and advancing therapies have greatly improved clinical outcomes, more than half of CRC patients demonstrate recurrence after initial treatments. The 5-year survival rate is only 14% for patients with distant metastasis [1]. Cancer-associated fibroblasts (CAFs) are the major components in the tumor microenvironment (TME), secreting active cytokines and growth factors to remodel the extracellular matrix and accelerate tumor progression [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%